The International Land Coalition - Independent Evaluation Group (Washington, DC: World Bank, 2017)
The organization, which is now called the International Land Coalition (ILC), was established on January 1, 1996, on the recommendation of the conference on hunger and poverty convened by the International Fund for Agricultural Development (IFAD) in 1995. At first, the organization was called the popular coalition to eradicate hunger and poverty. The ILC itself was formally constituted and launched along with its new name in February 2003. The mission of the land coalition has been to be a global alliance of intergovernmental, governmental and civil society organizations that worked together with rural poor people to increase their secure access to natural resources, especially land, and to enable them to participate directly in policy formulation and decision-making processes that affected their livelihood, at local, national, regional and international levels. From its inception through the end of 2007, the ILC has mobilized $18.6 million in donations and pledges receivable from donors. The major contributors have been International Fund for Agricultural Development (IFAD) (which has provided 48 percent of all resources), the Netherlands, the European Commission, Netherlands, the World Bank, Italy, and Belgium. The World Bank was a founding member and provided a one-time financial contribution of US$1.5 million from its development grant facility in 1998.